Contribution of linguistic meaning in inferring the denotation from words - Ameur Seddas (Journal of Informatics Education and Research, 2025)
This study aims to shed light on a topic closely related to the understanding of the meanings of the Arabic language, both in terms of words and structures, as well as to highlight the efforts of Arab scholars in semantics in serving Arabic vocabulary. The key to dealing with any human language initially lies in the word within and outside its context, in order to derive additional meanings through this precise step. This paper seeks to uncover the mechanisms of semantics, focusing specifically on the linguistic meaning within the framework of both ancient and modern studies from an Arab perspective, while also addressing some of its scattered elements found in lexicons and linguistic works. After reviewing and analyzing the examples and applying semantic mechanisms, it was concluded that activating, understanding, and tracing linguistic meaning helps in anticipating the perspectives of lexicographers, refining meanings, and moving beyond mere wording. All of this is achieved by examining the details of the lexical sources used, analyzing them, and deriving insights from them.